Evaluation of Psychology Master Program in Faculty of Education at King Saud University from The Viewpoint of The Students in The Light of The Academic Accreditation Standards - ELsayed Mohamed Abou Hashem (University of Science and Technology, Yemen, 2016)
Abstract:  The current research aims to evaluation the master's program in psychology at the Faculty of Education, King Saud University, from the viewpoint of the students in the light of the accreditation standards, and the sample consisted of 76 male and female students in all program pathways. They applied a questionnaire include seven axes represent aspects of the president of quality in graduate programs, namely: the objectives of the program, learning and teaching, curriculum, supervising scientific, faculty, admissions and registration procedures, facilities and equipment. And using frequencies, percentages and averages and graphs the results showed: - That the order of academic accreditation standards, according to the average calculation for the responses of students: faculty members with a mean (4.01), facilities and equipment (3.88), Admission (3.71), Learning and Teaching (3.66), the goals of the program (3.60), courses (3.36 ) and finally the scientific supervision (3.33). - That the level of program evaluation: (50.0%) believe that the program is very good compared to (38.2%) good, (7.9%) excellent, (3.9%) is weak. - That the degree of satisfaction with the program: (77.6%) satisfied with the program in return (22.4%) are dissatisfied with the program.